Penggunaan Media Flipbook Digital untuk Meningkatkan Motivasi Belajar Siswa Kelas V Sekolah Dasar Materi Cahaya dan Sifatnya - Meilinda, Ghina; Sunaengsih, Cucun; Sujana, Atep (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research has the main problem, namely the lack of use of digital media and the lack of motivation to learn in class V students at SD Negeri 1 Maniskidul. The aim of this research is to find out how learning is implemented using digital flipbook media and how students' learning motivation is after using digital flipbook media regarding light and its properties. The research method used is qualitative with a descriptive study design, data collection is carried out by observation, interviews and documentation. The research subjects studied were the class V homeroom teacher and class V students of SD Negeri 1 Maniskidul, totaling 30 people, namely 15 boys and 15 girls. The conclusion produced during the research was that the implementation of learning using digital flipbook media was researched through observations of teachers and class V students with very good results. Meanwhile, observations and interviews were carried out on fifth grade elementary school students with a total of 30 students, after using digital flipbook media there was an increase in motivation, the results became 2 categories derived from the learning motivation indicators themselves, namely 27 students who met the 8 indicators, and There were 3 students who met the 6 indicators.